Adherence to The World Cancer Research Fund/American Institute for Cancer Research 2018 Recommendations for Cancer Prevention and Risk of Colorectal Cancer - Petimar, Joshua (Cancer Epidemiol Biomarkers Prev, 2019)
BACKGROUND: The World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) 2018 diet, nutrition, and physical activity recommendations aim to reduce cancer risk. We examined adherence to the WCRF/AICR recommendations and colorectal cancer (CRC) risk in two prospective cohorts. METHODS: We followed 68,977 women in the Nurses’ Health Study and 45,442 men in the Health Professionals Follow-up Study from 1986 until 2012. We created cumulatively averaged WCRF/AICR scores using updated diet, adiposity, and physical activity data from questionnaires, and used Cox regression to estimate sex-specific hazard ratios (HR) and 95% confidence intervals (CI) for incident CRC. RESULTS: We documented 2,449 CRC cases. Men in the highest quintile of the WCRF/AICR lifestyle score had a lower risk of CRC compared to those in the lowest quintile (HR(Q5vsQ1)=0.64, 95% CI: 0.52–0.77). The result was weaker in women (HR(Q5vsQ1)=0.86, 95% CI: 0.72–1.02, P-heterogeneity by sex=0.006). When analyzing the diet recommendations alone, we similarly observed stronger inverse associations in men (HR(Q5vsQ1)=0.74, 95% CI: 0.61–0.90) compared to women (HR(Q5vsQ1)=0.93, 95% CI: 0.77–1.12, P-heterogeneity by sex=0.06). In men, the lifestyle score was more strongly inversely associated with risk of distal colon cancer compared to proximal colon or rectal cancer (P-common effects=0.03); we did not observe significant differences between anatomic locations in women. CONCLUSION: The 2018 WCRF/AICR cancer prevention recommendations are associated with lower CRC risk in men, with weaker results in women. IMPACT: Consideration of adiposity and physical activity in conjunction with diet is important for CRC prevention.